The effectiveness and safety of antifibrinolytics in patients with acute intracranial haemorrhage: statistical analysis plan for an individual patient data meta-analysis - Ker, Katherine; Prieto-Merino, David; Sprigg, Nikola; Mahmood, Abda; Bath, Philip M.W.; Kang Law, Zhe; Flaherty, Katie; Roberts, Ian (F1000Research, 2018)
Introduction: The Antifibrinolytic Trialists Collaboration aims to increase knowledge about the effectiveness and safety of antifibrinolytic treatment by conducting individual patient data (IPD) meta-analyses of randomised trials. This article presents the statistical analysis plan for an IPD meta-analysis of the effects of antifibrinolytics for acute intracranial haemorrhage. Methods: The protocol for the IPD meta-analysis has been registered with PROSPERO (CRD42016052155). We will conduct an individual patient data meta-analysis of randomised controlled trials with 1000 patients or more assessing the effects of antifibrinolytics in acute intracranial haemorrhage. We will assess the effect on two co-primary outcomes: 1) death in hospital at end of trial follow-up, and 2) death in hospital or dependency at end of trial follow-up. The co-primary outcomes will be limited to patients treated within three hours of injury or stroke onset. We will report treatment effects using odds ratios and 95% confidence intervals. We use logistic regression models to examine how the effect of antifibrinolytics vary by time to treatment, severity of intracranial bleeding, and age. We will also examine the effect of antifibrinolytics on secondary outcomes including death, dependency, vascular occlusive events, seizures, and neurological outcomes. Secondary outcomes will be assessed in all patients irrespective of time of treatment. All analyses will be conducted on an intention-to-treat basis. Conclusions: This IPD meta-analysis will examine important clinical questions about the effects of antifibrinolytic treatment in patients with intracranial haemorrhage that cannot be answered using aggregate data. With IPD we can examine how effects vary by time to treatment, bleeding severity, and age, to gain better understanding of the balance of benefit and harms on which to base recommendations for practice.